(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
The operation of currently widespread wireless data transmission methods, such as 3G, LTE, Wi-Fi, etc., is based on the use of radio frequency channels. Furthermore, the rapid increase in the speed of information exchange on the Internet motivates scientific research in the field of information exchange. Such technologies are less common at present, but a promising alternative to Li-Fi, which is based on the energy of light. In addition to the above, Li-Fi optical wireless technology can be used without restriction in places where the use of equipment that emits extraneous radio waves that may interfere with the normal operation of critical equipment is prohibited. Such places, of course, include intensive care wards of medical institutions, aircraft cabins and some other places.